Hubungan Ketergantungan Activity Daily Living Penderita Stroke dengan Beban Family Caregiver di Puskesmas Kasihan II - Siti Mulyani; Miftafu Darussalam (PSIK FKKMK UGM, 2023)
Background: Stroke can cause chronic neurological disorders that can cause physical changes and decline, especially in activities of daily living or Activity Daily Living (ADL). Prolonged ADL dependence has the potential to cause a burden for family caregivers.Objective: To determine the correlation between ADL dependence of patients with stroke and the burden of family caregivers.Method: This research was a correlational analytic quantitative study with a cross sectional design. The research was conducted in the working area of the Kasihan Health Center II in Bantul. There were 40 family caregivers and patients with stroke, as respondents. Samples were taken by simple random sampling technique. The research instruments were the Caregiver Reaction Scale (CRA) by Given and Barthel Index. Data analysis was performed with the Somers’d test.Result: most of the respondents with stroke were in mild dependence and were independent (f=18,45%), while family caregivers felt a moderate burden (f=29, 72,5%). The type of burden that the family caregiver felt the most was the burden of self-esteem with a mean score of 13,83. The Somers’d correlation test obtained the results for the value of r = 0,601, p-value = 0,000.Conclusion: There is a relationship between ADL dependency of patients with stroke and the burden of family caregivers with a moderate correlation level.ABSTRAKLatar belakang: Penyakit stroke dapat menyebabkan gangguan neurologis kronis yang dapat menimbulkan perubahan dan penurunan fisik terutama dalam aktivitas kehidupan sehari-hari atau activity daily living (ADL). Ketergantungan ADL dalam waktu yang lama berpotensi menimbulkan beban pada family caregiver.Tujuan: Untuk mengetahui hubungan ketergantungan ADL penderita stroke dengan beban family caregiver.Metode: Penelitian ini merupakan penelitian kuantitatif analitik korelasional dengan rancangan cross sectional. Penelitian dilakukan di wilayah kerja Puskesmas Kasihan II Bantul dengan responden family caregiver dan penderita stroke sejumlah 40 responden. Sampel diambil dengan teknik simple random sampling. Instrumen penelitian menggunakan Caregiver Reaction Scale (CRA) oleh Indeks Given dan Barthel. Analisis data dilakukan dengan uji Somers’d.Hasil: Sebagian besar responden penderita stroke termasuk dalam kategori ketergantungan ringan dan mandiri (f=18, 45%). Sementara family caregiver merasakan beban sedang (f=29, 72,5%). Jenis beban yang paling dirasakan oleh family caregiver adalah beban harga diri dengan mean score 13,83. Uji korelasi Somers’d didapatkan hasil nilai r=0,601 dan p=0,000.Kesimpulan: Terdapat hubungan antara ketergantungan ADL penderita stroke dengan beban family caregiver pada tingkat korelasi sedang.